Foxtail Millet as an Alternative to Groundnut under Rainfed Conditions - Deva, Sahaja; Lakshmi, R.Prasanna; Jyosthna, MK (Journal of Agricultural Extension Management, 2022)
Demonstrations were conducted at farmers fields at Guttapalem (Kalikiri mandal) and Murevandlapalli (Vayalpadu mandal) of Andra Pradesh during Kharif 2020-21 and 2021-22 in 4.0 ha area during each year to study the performance of improved variety of Foxtail millet (SiA 3156) as an alternative to traditional crop groundnut under rainfed conditions. Under demonstrations treatment comprised of Foxtail millet variety SiA 3156 which matures in 85-90 days with an average yield potential of 20-25 q/ha and compared with groundnut variety Kadiri 6. Foxtail millet performed well under rainfed situations where crop failure of groundnut was occurred. Pooled data of two years proved that Net returns and B: C ratio of foxtail millet were significantly higher than Groundnut variety Kadiri 6. Foxtail millet var SiA 3156 recorded 15750 Rs./ha net returns and B:C ratio of 2.1. Whereas, Groundnut var Kadiri 6 recorded net returns and B: C ratio of 1150 Rs./ ha and 1.0, respectively.